Fostering character through Pancasila and Civic Education in the digital era at Labschool Senior High School, Unsyiah - Rawandi, Fathur; Ruslan, Ruslan; Ali, Hasbi (Jurnal Geuthèë: Penelitian Multidisiplin, 2025)
This study focuses on the role of teachers in fostering and shaping students' character in response to the challenges of the current digital era through Pancasila and Civic Education. The objectives of this research are to: (1) describe the role of teachers in character development in the digital era, (2) identify the forms of character development implemented by teachers, and (3) examine the challenges and obstacles faced by teachers in the character development process. This research employs a qualitative approach with a descriptive research design. The subjects of this study include Civics Education teachers and 11th-grade students from Labschool Senior High School, Unsyiah. Data collection techniques are triangulated, combining observations, interviews, and document analysis. Data analysis procedures involve data reduction, data presentation, and conclusion drawing. The findings of this study indicate that (1) in the digital era, teachers play a crucial role as mentors, facilitators, and role models in fostering students' character, (2) the forms of character development implemented by teachers include the application of interactive teaching methods, such as group discussions and collaborative projects, to help students learn teamwork and appreciate differences, as well as integrating character values into the curriculum, and (3) the primary challenges in character development include students' susceptibility to negative content on social media, such as the spread of false information.